Transforming Performance Management: From Evaluation to Development, a Human Resource Approach to Maximizing Employee Potential - Ernest Hemingway, Tennessee Williams, Arthur Miller (International Journal of Innovative and Applied Finance, 2019)
login and register and pay the fees to get open access to content